THE ASSOCIATION BETWEEN DEPRESSION AND SELF-REPORTED SLEEP QUALITY AMONG HYPERTENSIVE PATIENTS IN A RURAL AREA OF CENTRAL SULAWESI - Ferdy Lainsamputty; Indrawan Manitu; Nur Abdillah (NUTRIX, 2019)
Poor quality of sleep may increase burden of hypertensive patients and worsen quality of life. Recognition of individuals’ sleep quality and its related factors might benefit the outcome of hypertension management. The purpose of this study was to investigate the association between depression and sleep quality among hypertensive patients in rural community. A cross-sectional, correlational study design was performed with 149 accidental samples at two public health care areas. Instruments included Depression Anxiety Stress Scale 42 and Pittsburgh Sleep Quality Index. Almost 78% of participants experienced mild to moderate depression and 98.7% of poor sleepers were identified. Significant determinants of sleep quality were exercises and type 2 diabetes mellitus (DM). Depression was associated to sleep quality but was not identified as a determinant. This study suggests future interventions should be directed to increase regular exercises and controlling co-existing disease particularly type 2 DM should be developed to improve sleep quality. Keywords: Depression, hypertension, sleep quality. Abstrak Kualitas tidur yang buruk dapat memperberat beban pasien hipertensi dan menurunkan kualitas hidup. Mengidentifikasi kualitas tidur individu dan faktor-faktor yang terkait dengannya dapat membantu meningkatkan hasil dari manajemen penyakit hipertensi. Penelitian ini bertujuan untuk menginvestigasi asosiasi depresi dan kualitas tidur pada pasien hipertensi di daerah pedesaan. Desain penelitian menggunakan pendekatan potong lintang dan deskriptif korelasi dengan 149 sampel insidental pada wilayah kerja dua pusat kesehatan masyarakat. Kuesioner yang digunakan yaitu DASS-42 dan PSQI. Hampir 78% partisipan menderita depresi ringan hingga sedang dan presentase kualitas tidur buruk sebanyak 98.7%. Faktor determinan yang signifikan adalah olahraga dan DM tipe 2. Depresi berhubungan secara signifikan dengan kualitas tidur, tetapi tidak teridentifikasi sebagai faktor determinan. Penelitian ini merekomendasikan dilakukannya intervensi untuk meningkatkan kegiatan olahraga yang regular dan pengontrolan penyakit komorbiditas terutama DM tipe 2 untuk meningkatkan kualitas tidur. Kata Kunci: Depresi, hipertensi, kualitas tidur.